2015
DOI: 10.3109/02688697.2014.997664
|View full text |Cite
|
Sign up to set email alerts
|

Recording stereoscopic 3D neurosurgery with a head-mounted 3D camera system

Abstract: Stereoscopic three-dimensional (3D) imaging can present more information to the viewer and further enhance the learning experience over traditional two-dimensional (2D) video. Most 3D surgical videos are recorded from the operating microscope and only feature the crux, or the most important part of the surgery, leaving out other crucial parts of surgery including the opening, approach, and closing of the surgical site. In addition, many other surgeries including complex spine, trauma, and intensive care unit p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Five of the nine articles (56%) were primary clinical research articles that evaluated various GoPro devices 35 38 39 42 43. All of these studies found that the technical specifications of the models tested could be adjusted to optimise the quality of picture and video capture such that fine details within the surgical field could be visualised.…”
Section: Resultsmentioning
confidence: 99%
“…Five of the nine articles (56%) were primary clinical research articles that evaluated various GoPro devices 35 38 39 42 43. All of these studies found that the technical specifications of the models tested could be adjusted to optimise the quality of picture and video capture such that fine details within the surgical field could be visualised.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of camera-positioning configurations discussed in the included articles was n = 128. The most common camera position was head mounted (60%, n = 77), 10-80 followed by fixed or tripod positioning (20%, n = 25), 35,62,…”
Section: Resultsmentioning
confidence: 99%
“…The GoPro is a small, lightweight, high-resolution action camera once mainly used by hobbyists in action sports, but has increasingly been utilised for a range of clinical education settings [6][7][8][9]. When worn with a head mount, it has a 149-degree wide-angle field of view that can capture the majority of visual information available to the wearer.…”
Section: Introductionmentioning
confidence: 99%